2011
DOI: 10.1007/s00590-011-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

Locking compression plate breakage and fracture non-union: a finite element study of three patient-specific cases

Abstract: Background & purpose The locking compression plate (LCP) system oVers a number of advantages in fracture Wxation combining angular stability through the use of locking screws with traditional Wxation techniques. However, the system is complex, requiring careful attention to biomechanical principles and good surgical technique. Methods From a series of clinical cases, where locking plate Wxation was used in fractures of long bones, three were selected. Patient-speciWc geometric information was obtained from AP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Similarly, Moazen et al concluded that the bridging length made a more substantial difference to the stiffness and interfragmentary movement than varying the plate material, plate thickness, or screw‐plate fixation . Also Nassiri et al have recently reported similar findings . The calculations of Boccaccio et al indicated that the presence of percutaneous fixation devices significantly shortened the healing times of the fractured body of the L4 vertebra .…”
Section: Computational Modeling Of Bone Regenerationmentioning
confidence: 89%
“…Similarly, Moazen et al concluded that the bridging length made a more substantial difference to the stiffness and interfragmentary movement than varying the plate material, plate thickness, or screw‐plate fixation . Also Nassiri et al have recently reported similar findings . The calculations of Boccaccio et al indicated that the presence of percutaneous fixation devices significantly shortened the healing times of the fractured body of the L4 vertebra .…”
Section: Computational Modeling Of Bone Regenerationmentioning
confidence: 89%
“…Hardware failure (plate failure, or screw breakage) is a complication that has been reported to occur in as many as 18% of plate fixations, 17 often as a result of an inappropriate fixation technique, rather than the choice of plate.…”
Section: Discussionmentioning
confidence: 99%
“…The use of locked screws at the level of the fracture passing through the fracture line and short working lengths are examples of such inappropriate techniques, 17 as it reduces the flexibility of the implant 8 which hinders the micromotion needed for callus formation.…”
Section: Discussionmentioning
confidence: 99%
“…They give excellent clinical and functional results in management of peri‐ and intra‐articular fractures provided they are applied with proper understanding of biomechanics; however, their advantages appear to be offset by difficulties in fracture reduction and plate application. Working length and position of screws are the most crucial factors for preventing implant failure and nonunion. An increase in working length increases inter fragmentary motion in comminuted fractures and also distributes stress over a large area.…”
Section: Discussionmentioning
confidence: 99%